Seeing Through the Veil : Optical Theory and Medieval Allegory - Akbari, Suzanne Conklin (Book collections on Project MUSE., 2004)
"In Seeing through the Veil, Suzanne Conklin Akbari examines several late medieval allegories in the context of contemporary paradigm shifts in scientific and philosophical theories of vision." "Offering a new interdisciplinary, synthetic approach to late medieval intellectual history and to major works within the medieval literary canon, Seeing through the Veil will be an essential resource to the study of medieval literature and culture, as well as philosophy, history of art, and history of science."--Jacket.